From Prison to Home - Films Media Group (2007)
Ex-convicts face formidable odds, and for African-Americans, conditions are usually even more difficult. This documentary traces the experiences of four black ex-inmates over the course of a year, focusing on their challenges with employment, housing, addiction, and reconnecting with family-as well as their participation in the nontraditional African American Program for parolees. Richard, a 36-year-old crack addict, has spent 12 years in and out of the system. Arthur, 45, has been arrested 13 times. Calvin, 49, has served 18 months for drug possession and burglary. And 37-year-old Randy, emerging for the first time after a 16-year murder sentence, is intent on going to college. The parole officers who work with these men are also interviewed. (71 minutes).
fma39056
Mode of access: World Wide Web.
System requirements: Windows Media, etc.